Effect of controlled release of HGF on extracellular vesicle secretion by urine-derived stem cells - Alwan, Abdelrahman; Khalil, Fatma; Bowlby, Joshua; Peko, Gabrielle; Estrada, Exel Valle; Singh, Sangeeta; Deep, Gagan; Zhang, Yuanyuan; Farney, Alan C.; Opara, Emmanuel C. (Frontiers in Bioengineering and Biotechnology, 2024)
introduction: The hepatic growth factor (HGF) stimulates DNA synthesis and cell proliferation and plays a role in tissue protection and regeneration. In this study, we have examined the effect of incubation of HGF with urine-derived stem cells (USC) on the secretion of small extracellular vesicles (sEV) by the cells. Materials and Methods: HGF in the incubation medium was either a bolus administration or a controlled release of an equivalent amount from microbeads within the size range of 50-200 µm made with ultrapurified low viscosity high-guluronic acid (UP-LVG) alginate. The incubations of USC with or without HGF were 3 days or 7 days before removal of the incubation media for harvesting sEV by precipitation method. Protein content of isolated sEV was measured by BCA assay for these three groups: control (no HGF-beads), bolus HGF, and HGF-beads. We also performed nanoparticle-tracking analysis (NTA), Western Blot assay and ELISA for HGF content of samples. Results: We found a significantly higher concentration of proteins in the HGF microbeads (control release group) compared to the bolus group and the control group after 7 days (p<0.0017). The NTA data aligned with the BCA as it showed a significantly higher concentration of particles within the size range of sEV (<200 nm) in the group treated with HGF beads compared to the two other groups on day 7 (p<0.0001). Conclusion: we found that administration of HGF to USC by controlled release of the growth factor significantly enhances the levels of sEV secretion during 7 days of incubation.